Simple methods for crossing and genetic analysis of Neurospora crassa strains - N. N. Pandit; V. E.A. Russo (Fungal Genetics Reports, 1993)
In the asexual cycle of Neurospora crassa, the wild-type strains produce only mycelia and conidia when grown at 30o-34oC. In contrast, during the sexual cycle the female reproductive structures - protoperithecia - can be produced and fertilized successfully only if the incubation temperature is around 25oC. Normally, a large number of conidia are also produced at this low temperature.